VD_FINDINFO Arrêt / 2018 / 984 vom 15. November 2018 - VD Tribunal cantonal (2018)
TRIBUNAL FÉDÉRAL, ADMISSION DE LA DEMANDE, FRAIS JUDICIAIRES, DÉPENS | 69 al. 1bis LAI, 61 let. a LPGA, 49 al. 1 LPA-VD